Young adult binge drinkers have immunophenotypic changes in peripheral polymorphonuclear cells and monocytes. (4th May 2018) - Pérez-García, Adolfo; Arroyo-Valerio, América Guadalupe; Zaldivar-Fujigaki, José Luis; Bustos-Esquivel, Mayra A.; Gastelum-Strozzi, Alfonso; Padilla-Castañeda, Miguel A.; Reding-Bernal, Arturo; Kershenobich, David; Hernández-Ruiz, Joselín
ABSTRACT: Background : High alcohol intake on weekends (binge drinking) is more frequent in young adults, who could undergo early liver damage. Alcohol-induced liver damage is characterized by polymorphonuclear cell (PMN) infiltration, which can be represented in the peripheral blood by altered trafficking and activation profiles. Objective : To evaluate the PMN trafficking and activation immunophenotypic profiles in people with a binge drinking pattern. Methods : People with binge drinking ( n = 18, 8 females) or at low risk ( n = 16, 13 females) based on their AUDIT and HEPCA scores were studied. Hematic biometry and liver enzyme tests were conducted. Peripheral blood leukocytes were stained for CCR5, CCR4, and CXCR4 (trafficking) and CD69 and CD127 (activation). PMNs and monocytes were analyzed by FACS. The data were analyzed using the T-test and Mann–Whitney's U-test for contrasts and principal component and Fuzzy C means analyses for clustering, with p < 0.05 considered significant. Results : Compared to the low-risk group, the binge group showed higher CCR5 expression on PMNs, decreases in the CD69 percentage and positive PMNs per microliter, and decreased CXCR4 expression on monocytes. Six immunophenotypical clusters were identified, all of which were distributed following the CCR5 and CXCR4 main vectors. Conclusion : Young adult binge drinkers have differential PMN trafficking and activation immunophenotypes, which could be related to the initial onset of alcoholic liver disease and a systemic inflammatory state in response to their alcohol consumption pattern. These findings could lead to the future development of an early diagnostic tool.